Negative electrode and battery
Patent Information
- Application Number
- CN202411621879.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-14
AI Technical Summary
The cycle stability of graphite silicon negative electrode materials in existing lithium-ion batteries is poor, resulting in a decrease in the capacity of the battery during charging and discharging, which cannot meet the needs of range and energy density.
By providing a coating in the negative electrode sheet, the coating comprises graphite and silicon-based material, and by defining the volume expansion coefficient A of the silicon-based material and the hardness coefficient B of the graphite, it satisfies 16≤A*B/0.15≤21 Functional relationships to improve cycle stability.
Without losing energy density and gram capacity, the cycle stability of graphite and silicon-based materials in lithium-ion batteries is significantly improved and the cycle life of the battery is extended.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode sheet and a battery. Background Art
[0002] The transition from fossil energy to new energy has become a trend. Under this trend, new energy vehicles powered by clean energy such as lithium batteries or hydrogen energy have emerged. Since lithium batteries are easier to commercialize than hydrogen energy, new energy vehicles are still mainly lithium batteries. However, although the proportion of installed capacity of new energy vehicles is increasing year by year, it is still low compared to gasoline vehicles. This is because there are certain pain points in the performance of new energy vehicles themselves, such as users' concerns about the range, charging speed, safety and low temperature performance of new energy vehicles.
[0003] In order to solve these problems, it is necessary to improve the performance of the power source, that is, the battery itself. In terms of cruising range, it is necessary to increase the energy density of the battery, that is, to exert higher energy at the same volume ratio. This requires improvement in the overall structural design of the battery. As far as the battery negative electrode material is concerned, it is necessary to increase the gram capacity of the negative electrode, such as adding some silicon to the graphite negative electrode sheet. Although the theoretical gram capacity of silicon is very high, about ten times that of graphite, silicon itself has problems such as volume expansion and insufficient conductivity. In the related technology, it was found in the use of graphite silicon negative electrodes that by combining the use of graphite negative electrode materials and silicon-based materials, while the energy density was improved, the cycle stability had a certain decline, and could not fully meet the battery design requirements. Summary of the invention
[0004] In view of this, the present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the present invention provides a negative electrode sheet and a battery, which can maintain good cycle stability of the battery without substantially losing energy density and gram capacity.
[0005] In order to solve the above technical problems, this application is implemented as follows:
[0006] According to one aspect of the present application, an embodiment of the present application provides a negative electrode plate, the negative electrode plate comprising: a current collector, and a coating disposed on at least one side surface of the current collector along a thickness direction;
[0007] The coating includes an active substance;
[0008] The active material includes graphite and silicon-based material, wherein the volume expansion coefficient of the silicon-based material is A, and the hardness coefficient of the graphite is B, and the unit of B is g / cm 3 ;
[0009] A and B satisfy:
[0010] 16≤A*B / 0.15≤21.
[0011] In addition, the negative electrode sheet according to the present application may also have the following additional technical features:
[0012] In some embodiments, A is the full charge expansion ratio of the negative electrode plate when a silicon-based material is used as the active material, and the range of A is 1.5~2.0.
[0013] In some embodiments, B is the average value of the compaction density of graphite under different pressures, and the range of B is 1.55-1.70, in g / cm 3 ;
[0014] The pressure ranges from 1 to 5T.
[0015] In some of the embodiments, the silicon-based material includes at least one of ground silicon, vapor phase silicon carbon, silicon oxide, pre-lithium silicon oxide, or pre-magnesium silicon oxide.
[0016] In some embodiments, the graphite includes at least one of artificial graphite, natural graphite, modified graphite, fast-filled graphite or isostatic graphite.
[0017] In some of the embodiments, the mass ratio of the silicon-based material to graphite is (25-40): (60-75).
[0018] In some of the embodiments, the coating further includes a conductive agent and a binder.
[0019] In some embodiments, the binder includes at least two of polyacrylic acid, polyacrylonitrile, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, styrene-butadiene rubber or modified styrene-butadiene polymer.
[0020] In some embodiments, the conductive agent includes at least two of single-walled carbon nanotubes, oligo-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, graphyne, acetylene black, or Ketjen black.
[0021] In some embodiments, the mass ratio of the active material, the binder and the conductive agent is (93~97): (2~5): (0.5~2).
[0022] In some embodiments, the current collector includes at least one of copper foil, red copper foil, porous copper foil, foam nickel foil, foam copper foil or carbon-coated copper foil.
[0023] According to another aspect of the present application, an embodiment of the present application provides a battery, which includes the negative electrode plate described above.
[0024] Implementing the technical solution of the present invention has at least the following beneficial effects:
[0025] In the embodiments of the present application, the negative electrode plate provided can be used as the negative electrode in a battery such as a lithium-ion battery. The present application improves the problem of poor cycle stability of lithium-ion batteries containing a large amount of silicon-based materials (>25%) by limiting specific parameters of silicon-based materials and graphite in the negative electrode plate.
[0026] From the perspective of the electrode level, when there are more silicon-based materials in the negative electrode, a larger expansion force will be generated during the lithium insertion process. This expansion force will squeeze the surrounding graphite particles. During the continuous charging and discharging process, this expansion pressure will repeatedly squeeze the graphite, causing the graphite particles to peel off and no longer be able to reversibly deintercalate lithium, resulting in the deterioration of cycle stability.
[0027] This application uses different silicon-based materials with different expansion forces, and the hardness of graphite also has different characteristics. By measuring the expansion ratio of silicon-based materials and the hardness of graphite, and quantifying them through volume expansion coefficient and hardness coefficient, a certain functional relationship is satisfied, that is, the volume expansion coefficient A of silicon-based materials and the hardness coefficient B of graphite satisfy: 16≤A*B / 0.15≤21. In this way, silicon-based materials with greater expansion force can be matched with harder graphite, and silicon-based materials with relatively smaller expansion force can be matched with relatively softer graphite. The cycle degradation problem that occurs when graphite and silicon-based materials are used together can be improved with a relatively simple method without losing energy density and gram capacity.
[0028] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION
[0029] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.
[0030] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0031] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0032] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0033] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0034] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0035] In the related art, in order to improve the cycle stability of lithium batteries, the silicon-based materials or graphite in the silicon-carbon negative electrode materials are often modified to change the structure of the silicon-based materials and graphite, so as to achieve the purpose of firmly and evenly distributing the silicon-based materials on the surface of the graphite materials, avoiding the agglomeration of the silicon-based materials themselves and the peeling off from the graphite, and improving the cycle stability of lithium batteries. However, the existing modification process is too complicated and will further increase the preparation cost of lithium batteries.
[0036] In view of this, the present application provides a negative electrode plate, which can improve the cycle degradation problem when graphite and silicon-based materials are used together in a relatively simple way without sacrificing energy density and gram capacity. The specific technical solution is described below.
[0037] In some embodiments, the present application provides a negative electrode plate, the negative electrode plate comprising: a current collector, and a coating disposed on at least one side surface of the current collector along a thickness direction;
[0038] The coating includes an active substance;
[0039] The active material includes graphite and silicon-based material, wherein the volume expansion coefficient of the silicon-based material is A, and the hardness coefficient of the graphite is B, and the unit of B is g / cm 3 ;
[0040] A and B satisfy:
[0041] 16≤A*B / 0.15≤21.
[0042] In the embodiment of the present application, the negative electrode sheet includes a current collector and a coating (also called an active material layer) disposed on at least one side surface of the current collector along the thickness direction. The above-mentioned "coating disposed on at least one side surface of the current collector along the thickness direction" means that the coating can be disposed on one surface of the current collector along its own thickness direction, or on two surfaces of the current collector along its own thickness direction. The "surface" here can be the entire area of the current collector or a partial area of the current collector. For example, in the present embodiment, the surface can be a partial area of the current collector, and the remaining area of the current collector can be used to connect the pole lugs. The present application has no special restrictions on this, as long as the purpose of the present application can be achieved.
[0043] As an example, the current collector has two surfaces opposite to each other in its thickness direction, and the coating is disposed on the two opposite surfaces of the current collector. It is understood that in other embodiments, the coating can also be stacked on any one of the two surfaces of the current collector.
[0044] The active materials in the coating of the provided negative electrode plate include graphite and silicon-based materials, and the relationship between the volume expansion coefficient A of the silicon-based material and the hardness coefficient B of the graphite is defined. It can be applied in batteries such as lithium-ion batteries to alleviate the problems of poor cycle stability or low capacity of graphite silicon negative electrodes in existing lithium-ion batteries.
[0045] It is particularly noteworthy that in the embodiment of the present application, A and B satisfy: 16≤A*B / 0.15≤21; further, A and B satisfy: 17≤A*B / 0.15≤20. For example, the value of A*B / 0.15 can be any one of 16, 17, 18, 19, 20, 21 or a range of values between any two of them.
[0046] Therefore, the present application makes the volume expansion coefficient A of the silicon-based material and the hardness coefficient B of the graphite satisfy the above functional relationship, so that the silicon-based material with greater expansion force is matched with harder graphite, and the silicon-based material with relatively smaller expansion force is matched with relatively softer graphite. In the process of continuous charging and discharging, the delamination of graphite particles can be reduced, and then the cycle degradation problem that occurs when graphite and silicon-based materials are used together can be improved with a relatively simple method without losing energy density and gram capacity.
[0047] In the embodiment of the present application, the volume expansion coefficient A of the silicon-based material is the full charge expansion ratio of the negative electrode plate when only the silicon-based material is used as the active material.
[0048] In the embodiment of the present application, the range of A is 1.5~2.0; further, the range of A can be 1.6~1.9. For example, the value of A can be any one of 1.5, 1.6, 1.8, 1.9, 2.0 or a range between any two of them. In this way, by making the value of A within the above range, the requirements of the battery for energy density can be met at the same time, and the battery can also maintain a high cycle stability. If the value of A is too small, the gram capacity is relatively low, and it is difficult to meet the requirements for energy density in practical applications. If the value of A is too large, the material expands too much, the cycle performance is poor, and it cannot be used in practice.
[0049] In the embodiment of the present application, the volume expansion coefficient A of the silicon-based material is obtained by testing the full-charge expansion ratio of different negative electrode plates with gradient silicon-based material content ratios, obtaining a fitting relationship between the silicon-based material content and the expansion ratio, and then extrapolating the full-charge expansion ratio of the pure silicon-based material negative electrode to obtain the volume expansion coefficient A of the silicon-based material.
[0050] Exemplarily, in the process of testing the volume expansion coefficient A of the above silicon-based material, the mass percentage of the silicon-based material in the negative electrode sheet active material can be 40% to 75%, and the gradient difference can be 1% to 10%; further, the mass percentage of the silicon-based material in the negative electrode sheet active material is 45% to 60%, and the gradient difference is 2% to 5%. For example, the mass percentage of the silicon-based material in different negative electrode sheet active materials can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, and the gradient difference can be 1%, 2%, 4%, 5%, 6%, 8%, 10%.
[0051] Optionally, in some embodiments, the volume expansion coefficient A of the silicon-based material can be obtained in the following manner: using graphite and silicon-based materials as active materials for the negative electrode plates, preparing negative electrode plates containing gradient proportions of silicon-based materials (the number of negative electrode plates ≥ 5, for example, can be 5, 6, 7, 8, 9, 10), stacking the negative electrode plates, isolation films, and positive electrode plates in sequence, winding them to obtain bare cells, ultrasonically welding the tabs, placing the bare cells into a battery shell, drying to remove moisture, injecting electrolyte into the battery shell, encapsulating, and dividing the cells into components to obtain a secondary battery. When designing the gram capacity of the full-electric negative electrode, a series of gradient values are designed, such as 400, 450, 500, 550, 600, 650, 700, 750, etc. After the battery is divided into different capacities, it is fully charged. After being fully charged, it is disassembled to measure the thickness of the negative electrode plate, and the thickness is compared with the cold-pressed plate to obtain a series of expansion ratios. Then, the relationship between the silicon-based material content and the expansion ratio is fitted (the relationship is generally a linear relationship), and then the full-charge expansion ratio of the plate when only silicon-based materials are used as the active material of the negative electrode plate is extrapolated, which is the volume expansion coefficient A. Among them, the structure of the positive electrode plate and the structure of the separator can be the positive electrode plate structure and the separator structure that can be used for secondary batteries that are well known in the art, and this is not limited to this and will not be repeated here.
[0052] In addition, in some cases, the volume expansion coefficient A of the silicon-based material can also be obtained according to actual conditions and practical experience.
[0053] In the embodiment of the present application, B is the average value of the compaction density of graphite under different pressures. It should be understood that characterizing the hardness coefficient of graphite by using the average value of the compaction density of graphite under different pressures is a common characterization method in the art, which is more consistent with the actual situation of the pole piece during the cold pressing process, because relatively speaking, larger powders are easier to press when the pole piece is rolled, while smaller powders are more difficult to press when rolled.
[0054] The range of B is 1.55~1.70; further, the range of B can be 1.58~1.66. For example, the value of B can be any point value among 1.55, 1.57, 1.59, 1.60, 1.63, 1.65, 1.66, 1.68, 1.70 or any range value between two of them. In this way, by making the value of B within the above range, the requirements of the battery for energy density can be met at the same time, and the battery can also maintain a high cycle stability. The applicant found that if the value of B is too low, such as lower than 1.55, it means that the proportion of mosaic in the graphite raw material is higher, harder, and the gram capacity is lower; if the value of B is too high, such as higher than 1.70, it means that the proportion of fibrous components in the graphite raw material is higher, the degree of graphitization is higher, softer, and the gram capacity is higher; but on the other hand, there is an upper limit to the value of B, because graphite and silicon-based materials should not be too soft when combined, otherwise the volume expansion and contraction of silicon cannot be effectively suppressed.
[0055] In the present application, B is the average value of the compaction density of graphite under different pressures, in g / cm 3 Preferably, when calculating the density mean, the number of values taken is ≥ 5, for example, it can be 5, 6, 7, 8, 9, 10, etc.
[0056] In the embodiment of the present application, the pressure ranges from 1 to 5 T; further, the pressure ranges from 2 to 4 T. For example, the pressure value may be 1 T, 2 T, 3 T, 4 T, or 5 T.
[0057] That is, in the embodiments of the present application, the hardness coefficient of graphite is indirectly characterized by the compaction density of graphite powder. Generally, harder graphite will be less compacted, while softer graphite is easier to compress and has a larger compaction. For example, the hardness coefficient B of graphite is obtained by testing the compaction density of graphite under different pressures and then taking the average value, and its value range is 1.55≤B≤1.7; the different pressures can be 1T, 2T, 3T, 4T, 5T. In addition, other different specific pressure values can also be used according to actual conditions, such as 1T, 1.5T, 2T, 2.5T, 3T, 4T, etc., without limitation.
[0058] Optionally, in some embodiments, the compacted density (ρ=m / V=m / πr 2 h) can be obtained by the following method: weigh a certain mass of powder, load the graphite powder into the mold (such as loading the powder cylinder with a diameter of 13mm or other determined diameter values), monitor the height and pressure of the graphite column respectively through two sensors, and calculate the powder compaction density through the powder column height h (pressure relief stage). The program control is as follows:
[0059] 1) Initial control mode - displacement control (10 mm / min) Final control mode - force control (10000N);
[0060] 2) Initial control mode - force load maintenance (30s);
[0061] 3) Initial control mode - displacement control (30 mm / min) Final control mode - force control (20N);
[0062] 4) Initial control mode - force load maintenance (10s);
[0063] When testing the compaction density under other pressures, just change the pressure value in step 1). For example, repeat the test of the powder compaction density at 2T, 3T, 4T, and 5T.
[0064] It should be understood that the specific test method and program control principle of the compaction density are known to those skilled in the art, and the specific operation method and principle will not be described in detail.
[0065] In the embodiment of the present application, the silicon-based material includes but is not limited to at least one of ground silicon, gas-phase silicon carbon, silicon oxide, pre-lithium silicon oxide or pre-magnesium silicon oxide.
[0066] The silicon-based material may also be a micrometer-scale silicon material (micrometer silicon), or may also be a nanometer-scale silicon material (nano silicon).
[0067] The silicon oxide is conventional silicon oxide, such as ordinary silicon oxide without other metals. Pre-lithiation silicon oxide is pre-lithiation silicon oxide, and pre-magnesium silicon oxide is pre-magnesium silicon oxide.
[0068] Optionally, in an embodiment of the present application, the ground silicon is nano-silicon obtained by grinding, and the particle size range of the ground silicon (nano-silicon) can be 50nm~100nm.
[0069] In the embodiments of the present application, the graphite includes but is not limited to at least one of artificial graphite, natural graphite, modified graphite, fast-filled graphite or isostatic graphite.
[0070] The present invention does not limit the shapes of graphite and silicon-based materials. As an example, the shapes of graphite particles and silicon-based materials are selected from one or more of block, spherical and spherical. The shape of the particles will affect the compaction density.
[0071] Furthermore, the shapes of graphite and silicon-based materials can be spherical or quasi-spherical, which can better achieve the purpose of protecting silicon particles.
[0072] In the embodiment of the present application, the mass ratio of the silicon-based material to the graphite is (25-40): (60-75); as an example, the mass ratio of the silicon-based material to the graphite can be 25:75, 30:70, 32:68, 35:65, 38:62, 40:60, etc. In this way, during the volume expansion of the negative electrode, the stress can be well released, the possibility of silicon particles breaking can be reduced, and the cycle performance of the battery can be improved.
[0073] In an embodiment of the present application, the coating further comprises a conductive agent. As a non-limiting example, the conductive agent includes but is not limited to at least two of single-walled carbon nanotubes, few-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, graphyne, acetylene black or Ketjen black. Among them, the conductive carbon black may include acetylene black, Ketjen black, etc. As an example, the conductive agent includes at least one of single-walled carbon nanotubes, few-walled carbon nanotubes, multi-walled carbon nanotubes, and includes at least one of graphene, graphyne, acetylene black or Ketjen black.
[0074] The above-mentioned conductive agents include point conductive agents and long-range conductive agents. Preferably, the conductive agent includes both point conductive agents and long-range conductive agents. Therefore, the point conductive agent can be better coated on the surface of the active material, and can be used in coordination with the long-range conductive agent of carbon tubes with better conductivity to better improve the overall conductivity of the negative electrode sheet.
[0075] In the embodiment of the present application, the coating further comprises a binder. As a non-limiting example, the binder includes but is not limited to at least two of polyacrylic acid, polyacrylonitrile, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, styrene-butadiene rubber or modified styrene-butadiene polymer.
[0076] The combination of two or more types of adhesives can achieve better bonding. For example, polyacrylic acid adhesives have better dynamic properties but lack flexibility. Using them in conjunction with styrene-butadiene rubber adhesives, which are softer, can better improve the dynamic properties and flexibility of the adhesive.
[0077] Optionally, in the embodiments of the present application, the conductive agent can be used in any combination, and the binder can be used in any combination without special restrictions. As an example, single-walled carbon nanotubes and oligo-walled carbon nanotubes are mixed in any proportion as a conductive agent, and polyacrylic acid and polyacrylonitrile are mixed in any proportion as a binder; it can also be that single-walled carbon nanotubes, oligo-walled carbon nanotubes and graphene are mixed in any proportion as a conductive agent, and polyacrylic acid and lithium carboxymethyl cellulose are mixed in any proportion as a binder; it can also be that multi-walled carbon nanotubes, graphene, graphyne and acetylene black are mixed in any proportion as a conductive agent, and lithium carboxymethyl cellulose, styrene butadiene rubber and modified styrene butadiene polymer are mixed in any proportion as a binder.
[0078] In the embodiments of the present application, the mass ratio of the active material, the conductive agent and the binder is (93~97):(0.5~2):(2~5); as an example, the mass ratio of the active material, the conductive agent and the binder is 93:2:5, 95:1:4, 93:1:5, 96:1:3, 97:0.5:2.5, etc.
[0079] In the embodiment of the present invention, the current collector includes but is not limited to at least one of copper foil, red copper foil, porous copper foil, foam nickel foil, foam copper foil or carbon-coated copper foil.
[0080] Therefore, based on the above settings, the present invention improves the problem of poor cycle stability of lithium-ion batteries containing more silicon negative electrodes (>25%) by designing a negative electrode plate structure. When there are more silicon-based materials in the negative electrode plate, a larger expansion force will be generated during the lithium insertion process. This expansion force will squeeze the surrounding graphite particles. In the process of continuous charging and discharging, this expansion pressure will repeatedly squeeze the graphite, causing the graphite particles to peel off and no longer be able to reversibly deintercalate lithium, thereby causing the degradation of cycle stability. The present application has different expansion forces according to different silicon-based materials, and the hardness of graphite also has large and small characteristics. By measuring the expansion ratio of silicon-based materials and the hardness of graphite, and quantifying them through volume expansion coefficient and hardness coefficient, it satisfies a certain functional relationship. Let the silicon-based material with greater expansion force be matched with harder graphite. The harder graphite can withstand greater expansion force and undergo smaller deformation, thereby avoiding peeling between graphite particles. By pairing silicon-based materials with relatively smaller expansion forces with relatively softer graphite, the softer graphite will be subject to relatively smaller expansion forces, which can also prevent delamination between graphite particles.
[0081] In the embodiments of the present application, the method for preparing the negative electrode plate is a common method in the art, and there is no limitation on the specific operation method.
[0082] As an example, the present application provides a method for preparing a negative electrode sheet, the method comprising the following steps:
[0083] Mixing active material, binder, conductive agent and water to obtain negative electrode slurry;
[0084] After the negative electrode slurry is coated on the surface of the current collector, a negative electrode sheet is obtained.
[0085] It should be understood that the "method for preparing the negative electrode sheet" and the aforementioned "negative electrode sheet" are based on the same inventive concept, and all the features and advantages described above for the "negative electrode sheet" are also applicable to the "method for preparing the composite negative electrode sheet", which will not be repeated here one by one.
[0086] In the embodiment of the present application, the solid content of the negative electrode slurry is 47-55%; as an example, the solid content of the negative electrode slurry can be 47%, 48%, 50%, 52%, 55%, etc.
[0087] In an embodiment of the present invention, the coating is applied on at least one side of the current collector along the thickness direction; as an example, the coating is applied equally on both side surfaces of the current collector along the thickness direction.
[0088] In an embodiment of the present invention, the coating weight on a single side of the negative electrode plate is between 80-150 mg; as an example, the coating weight on a single side may be 80 mg, 90 mg, 100 mg, 120 mg, 150 mg, etc.
[0089] In the embodiment of the present application, the compaction density of the negative electrode sheet is 1.5-1.7 g / cm 3 As an example, the compaction density of the negative electrode sheet can be 1.5g / cm 3 , 1.55g / cm 3 , 1.60g / cm 3 , 1.65g / cm 3 , 1.70g / cm 3 In this range, the prepared negative electrode sheet has good porosity, and after being used in preparing a battery, the battery has excellent cycle performance and rate discharge performance.
[0090] In some embodiments, a battery is provided, the battery comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. Optionally, the battery may be a secondary battery, and the secondary battery may be a lithium-ion battery.
[0091] The main feature of the battery is that it includes any of the above-mentioned negative electrode plates of the present application. Due to the use of the negative electrode plates of this embodiment, the cycle degradation problem that occurs when graphite and silicon-based materials are used together can be improved in a relatively simple way without sacrificing energy density and gram capacity, thereby improving the cycle life of the battery.
[0092] In the embodiments of the present application, the structure of the positive electrode plate and the structure of the isolation membrane may be the positive electrode plate structure and the isolation membrane structure known in the art and can be used for secondary batteries, and are not limited to this and will not be described in detail here.
[0093] Example
[0094] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this area or the product instructions are used. If the manufacturer of the reagents, materials or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0095] Example 1
[0096] (1) Preparation of negative electrode slurry
[0097] According to the ratio, the active material and the conductive carbon black are pre-mixed, and then 1 / 2 part of polyacrylic acid and deionized water are added and stirred, and then the single-walled carbon nanotubes, the remaining 1 / 2 part of polyacrylic acid, styrene-butadiene rubber and deionized water are added and stirred to obtain a negative electrode slurry with a solid content of about 51%;
[0098] Among them, the mass ratio of active material, styrene-butadiene rubber, polyacrylic acid, single-walled carbon nanotubes and conductive carbon black is 94.3:1.4:2.8:0.06:1.44;
[0099] The active material is composed of pre-lithiated silicon oxide and artificial graphite, and the pre-lithiated silicon oxide and artificial graphite are formulated into a composite material with a gram capacity of 650 mAh / g according to their respective capacities (the mass ratio of pre-lithiated silicon oxide to artificial graphite is 30:70);
[0100] The volume expansion coefficient A of pre-lithium silicon oxide is 1.8, and the hardness coefficient B of artificial graphite is 1.58, in g / cm 3 (Same below); A*B / 0.15=18.96.
[0101] (2) Preparation of negative electrode sheet
[0102] The negative electrode slurry was coated on the copper foil with a single-side coating weight of 102.7 mg. After preliminary baking in an oven, the reverse side was coated with the same coating weight as the front side. After secondary drying, cold pressing (compacted density 1.6 g / cm 3 ), and obtain the negative electrode sheet.
[0103] Example 2
[0104] The difference between Example 2 and Example 1 is that the active material used is composed of gas phase silicon carbon and artificial graphite, and the gas phase silicon carbon and artificial graphite are prepared into a composite material with a gram capacity of 650 mAh / g according to their respective capacities;
[0105] Among them, the volume expansion coefficient A of gas phase silicon carbon is 1.5, and the hardness coefficient B of artificial graphite is 1.67; A*B / 0.15=16.70.
[0106] The rest are the same as in Example 1.
[0107] Example 3
[0108] The difference between Example 3 and Example 1 is that:
[0109] The volume expansion coefficient A of pre-lithium silicon oxide is 1.65, and the hardness coefficient B of artificial graphite is 1.62; A*B / 0.15=17.82.
[0110] The rest are the same as in Example 1.
[0111] Example 4
[0112] The difference between Example 4 and Example 1 is that,
[0113] The silicon-based material uses gas phase silicon carbon, the volume expansion coefficient A of gas phase silicon is 1.5, and the hardness coefficient B of artificial graphite is 1.6; A*B / 0.15=16.00.
[0114] The rest are the same as in Example 1.
[0115] Example 5
[0116] The difference between Example 5 and Example 1 is that
[0117] The volume expansion coefficient A of pre-lithium silicon oxide is 2.0, and the hardness coefficient B of artificial graphite is 1.58; A*B / 0.15=21.07.
[0118] The rest are the same as in Example 1.
[0119] Example 6
[0120] The difference between Example 6 and Example 1 is that the active material used is composed of ground silicon and natural graphite, and the ground silicon and natural graphite are prepared into a composite material with a gram capacity of 650 mAh / g according to their respective capacities;
[0121] Among them, the volume expansion coefficient A of ground silicon is 1.8, and the hardness coefficient B of natural graphite is 1.58; A*B / 0.15=18.96.
[0122] Example 7
[0123] The difference between Example 7 and Example 1 is that the active material used is composed of silicon oxide and modified graphite; and silicon oxide and modified graphite are prepared into a composite material with a gram capacity of 650 mAh / g according to their respective capacities;
[0124] Among them, the volume expansion coefficient A of silicon oxide is 1.8, and the hardness coefficient B of modified graphite is 1.58; A*B / 0.15=18.96.
[0125] Example 8
[0126] The difference between Example 8 and Example 1 is that,
[0127] Pre-lithiation silicon oxide and artificial graphite are formulated into a composite material with a gram capacity of 750 mAh / g according to their respective capacities (the mass ratio of pre-lithiation silicon oxide and artificial graphite is 40:60); the mass ratio of active substance, styrene-butadiene rubber, polyacrylic acid, single-walled carbon nanotube and conductive carbon black is 93.9:1.4:3.2:0.06:1.44.
[0128] Example 9
[0129] The difference between Example 9 and Example 1 is that
[0130] Pre-lithiation silicon oxide and artificial graphite are formulated into a composite material with a gram capacity of 550 mAh / g according to their respective capacities (the mass ratio of pre-lithiation silicon oxide and artificial graphite is 20.5:79.5); the mass ratio of active substance, styrene-butadiene rubber, polyacrylic acid, single-walled carbon nanosilicon and conductive carbon black is 94.7:1.2:2.6:0.06:1.44.
[0131] Example 10
[0132] The difference between Example 10 and Example 1 is that
[0133] The active material and the conductive carbon black are pre-mixed, and then 1 / 2 part of sodium carboxymethyl cellulose and deionized water are added and stirred, and then multi-walled carbon nanotubes, the remaining 1 / 2 part of sodium carboxymethyl cellulose, styrene-butadiene rubber and deionized water are added and stirred to obtain a negative electrode slurry with a solid content of about 51%;
[0134] Among them, the mass ratio of active substance, styrene-butadiene rubber, sodium carboxymethyl cellulose, multi-walled carbon nanotubes and conductive carbon black is 94.3:1.4:2.8:0.06:1.44.
[0135] The rest are the same as in Example 1.
[0136] Comparative Example 1
[0137] The difference between Comparative Example 1 and Example 1 is that
[0138] The volume expansion coefficient A of pre-lithium silicon oxide is 1.9, and the hardness coefficient B of artificial graphite is 1.7; A*B / 0.15=21.53.
[0139] The rest are the same as in Example 1.
[0140] Comparative Example 2
[0141] The difference between Comparative Example 2 and Example 2 is that,
[0142] The volume expansion coefficient A of gas phase silicon carbon is 1.5, and the hardness coefficient B of artificial graphite is 1.55; A*B / 0.15=15.50.
[0143] The rest is the same as Example 2.
[0144] Comparative Example 3
[0145] The difference between Comparative Example 3 and Example 2 is that,
[0146] The silicon-based material uses gas phase silicon carbon, the volume expansion coefficient A of gas phase silicon carbon is 1.4, and the hardness coefficient B of artificial graphite is 1.5; A*B / 0.15=14.00.
[0147] The rest is the same as Example 2.
[0148] Comparative Example 4
[0149] The difference between Comparative Example 1 and Example 1 is that
[0150] The volume expansion coefficient A of pre-lithium silicon oxide is 2.1, and the hardness coefficient B of artificial graphite is 1.8; A*B / 0.15=25.20.
[0151] The rest are the same as in Example 1.
[0152] Performance Testing
[0153] 1. Preparation of lithium batteries:
[0154] (1) Preparation of positive electrode sheet: A mixture of eight series nickel-cobalt-manganese material, PVDF, conductive carbon black and carbon nanotubes in a mass ratio of 0.978:0.009:0.008:0.005 was homogenized to obtain a positive electrode slurry; the positive electrode slurry was coated on aluminum foil with a coating surface density of 0.3 g / m 2 , double-sided coating, drying and roll pressing to obtain the positive electrode sheet, the compaction density is 3.4 g / cm 3 .
[0155] (2) Preparation of isolation film: An isolation film comprising a polypropylene base film and a coating of aluminum oxide was used, wherein the thickness of the polypropylene base film was 12 μm and the thickness of the coating was 3 μm.
[0156] (3) Preparation of electrolyte: Ethylene carbonate (EC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC) are mixed in a volume ratio of 1:1:1. Then, fully dried lithium hexafluorophosphate is dissolved in a mixed organic solvent at a ratio of 1.2 mol / L. Vinylidene carbonate is added to prepare an electrolyte.
[0157] (4) The negative electrode sheets prepared in the above embodiments and comparative examples are stacked, wound with the separator and the positive electrode sheets in sequence to obtain a bare cell, and the tabs are ultrasonically welded. The bare cell is placed in a battery case, dried to remove moisture, and an electrolyte is injected into the battery case, which is packaged and divided into different capacities to obtain a lithium secondary battery.
[0158] 2. Test the electrochemical performance of the battery:
[0159] (1) First discharge capacity and first charge capacity: During formation charge, first charge to 3.4V at 0.02C constant current, then charge to 3.75V at 0.1C constant current. During capacity division, first charge to 4.25V at 0.5C constant current, then charge at constant voltage until the current decreases to 0.05C. Then, discharge at 1C constant current, then discharge at 0.2C constant current to 2.5V. The charge and discharge gram capacities are obtained by dividing the charge and discharge capacities by the mass of the active material.
[0160] (2) First coulombic efficiency test: First coulombic efficiency = first discharge capacity / first charge capacity*100%.
[0161] The test results are shown in Table 1.
[0162] Table 1 Gram capacity and first coulombic efficiency of each embodiment and comparative example
[0163]
[0164] As can be seen from Table 1, the first charge capacity of the embodiment and the comparative example is relatively close, and the main difference is the first discharge capacity and the first coulombic efficiency. Embodiments 1 to 3 show similar reversible capacity and first coulombic efficiency because of the reasonable combination of silicon material and graphite. The first efficiency of embodiment 4 is slightly lower, and the first efficiency of embodiment 5 is slightly higher, mainly because it is closer to the endpoint value. Graphite is harder and generally the first efficiency will be slightly lower. The larger the silicon oxide domain, the higher the first efficiency. The discharge capacity and first efficiency of embodiment 7 are the lowest because its silicon negative electrode material is silicon oxide without pre-lithium. The negative electrode gram capacity of embodiments 1, 8 and 9 is designed to be 650mAh / g, 750mAh / g and 550mAh / g, respectively. It can be seen from the data in Table 1 that the higher the gram capacity, the lower the first efficiency and the lower the reversible capacity. The reversible capacity and first coulombic efficiency of Comparative Example 1 are slightly higher than those of Examples 1 to 3, mainly because the volume expansion coefficient of the pre-lithium silicon oxide it matches is higher, the silicon domain inside it is larger, the first efficiency is higher, and the hardness coefficient of graphite is also higher, which also brings less irreversible capacity consumption. In contrast, Comparative Example 2 has lower discharge capacity and first coulombic efficiency because the matched silicon material is gas phase silicon carbon, and the lower volume expansion coefficient brings lower first efficiency, and the matched graphite has a lower hardness coefficient and a lower degree of graphitization, which also reduces the first coulombic efficiency. The first efficiency and reversible capacity of Comparative Example 3 are slightly lower than those of Comparative Example 2, mainly because its lower expansion coefficient of gas phase silicon carbon and harder graphite will cause difficulty in rolling the pole piece, particle breakage, and thus loss of gram capacity. Comparative Example 4 is similar to Comparative Example 1 and Comparative Example 1 is similar to Example 1.
[0165] (3) Cycle performance test: At room temperature 25°C, the starting and ending voltages are 2.8 V and 4.25 V, respectively. Charge at 1C to 4.25 V, then charge at 4.25 V constant voltage until the current decreases to 0.05 C, and discharge at 1C to 2.8 V. Record the ratio of the discharge capacity to the initial discharge capacity in each cycle, and record the number of cycles at different capacity retention rates (such as 90%, 85% and 80%).
[0166] The test results are shown in Table 2.
[0167] Table 2 Electrical properties of various embodiments and comparative examples
[0168]
[0169] As can be seen from Table 2, the matching of different silicon-based materials and graphite is quite different. The silicon-based materials used in Example 1, Example 3, Example 5, Example 8, Example 9, Example 10, Comparative Example 1, and Comparative Example 4 are pre-lithium silicon oxide, while the silicon-based materials used in Example 2, Example 4, Comparative Example 2 and Comparative Example 3 are gas-phase silicon carbon. In addition, Example 6 uses nano silicon carbon, and Example 7 uses silicon oxide without pre-lithium. In comparison, from the perspective of cycle stability, gas-phase silicon carbon is overall greater than silicon oxide without pre-lithium, greater than pre-lithium silicon oxide, and greater than nano silicon materials. From the perspective of classification, the cycle stability of Example 1, Example 3, Example 5, Example 8, Example 9 and Example 10 is much better than that of Comparative Example 1 and Comparative Example 4, which is mainly due to the reasonable matching of pre-lithium silicon oxide and graphite. The matching of pre-lithium silicon oxide with a larger volume expansion coefficient and harder artificial graphite can well buffer the squeezing of graphite particles by silicon oxide during continuous circulation, so as not to cause graphite to crack and lose active capacity, thereby significantly improving the cycle stability. Relatively speaking, the cycle stability of Example 9 is the best because its gram capacity is the lowest, which is 550 mAh / g, and the cycle stability of Example 8 is the worst because its gram capacity is the highest, which is 750 mAh / g. The cycle stability of Example 7 is greater than that of Example 1, mainly because its silicon negative electrode material is unpre-lithiumated silicon oxide, and the silicon crystal domains are less electrochemically agglomerated during the cycle, which improves the cycle stability to a certain extent.
[0170] In addition, the cycle stability of Example 2 is better than that of Example 4, and both are better than Comparative Example 2. The cycle stability of Comparative Example 2 is better than that of Comparative Example 3. The reasons are consistent. When the volume expansion coefficient of the gas phase silicon carbon material is too low and the compaction density of graphite is too low, it means that both types of materials are very hard and difficult to press during pole piece rolling. The active substances therein are easily crushed, resulting in a decrease in cycle stability.
[0171] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0172] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. must be possessed by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and facilitation of understanding, rather than limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.
[0173] It should be noted that the term "and / or" or " / " used in this document is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The singular forms of "a", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0174] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0175] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A negative electrode plate, characterized in that: It comprises a current collector and a coating disposed on at least one side of the current collector along the thickness direction; The coating includes an active substance; The active material comprises graphite and silicon-based material, and the mass ratio of the silicon-based material to graphite is (25-40): (60-75); The volume expansion coefficient of the silicon-based material is A, the hardness coefficient of the graphite is B, and the unit of B is g / cm 3 ; A and B satisfy: 16≤A*B / 0.15≤21; A is the full charge expansion ratio of the negative electrode plate when a silicon-based material is used as the active material, and the range of A is 1.5 to 2.0; B is the average value of the compaction density of graphite under different pressures, and the range of B is 1.55~1.70; wherein the range of the pressure is 1~5T.
2. The negative electrode sheet according to claim 1, characterized in that: The silicon-based material includes at least one of ground silicon, vapor phase silicon carbon, silicon oxide, pre-lithium silicon oxide or pre-magnesium silicon oxide.
3. The negative electrode sheet according to claim 1, characterized in that: The graphite includes at least one of artificial graphite or natural graphite.
4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The coating also includes a conductive agent and a binder; The binder comprises at least two of polyacrylic acid, polyacrylonitrile, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, styrene-butadiene rubber or modified styrene-butadiene rubber; And / or, the conductive agent includes at least two of single-walled carbon nanotubes, few-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, graphyne, acetylene black or Ketjen black.
5. The negative electrode sheet according to claim 4, characterized in that: The mass ratio of the active material, the binder and the conductive agent is (93-97): (2-5): (0.5-2).
6. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The current collector includes at least one of copper foil, red copper foil or foam nickel foil.
7. A battery comprising a negative electrode plate, characterized in that: The negative electrode plate comprises the negative electrode plate according to any one of claims 1 to 6.
Citation Information
Patent Citations
Lithium ion battery silicon negative electrode material, and preparation method and application thereof
CN107863497A
Negative pole piece of lithium ion battery, and lithium ion battery using the negative pole piece
CN109585781A